Aksin graphic Sdn. Bhd. / Kamal Rasyid Samsudin ... [et al.] - Samsudin, Kamal Rasyid; Mohd. Radzi, Idi Ashikin; Ahmad, Shahrul Nizam; Abd. Rahman, Azlan Shah; Dzulkefli, Mohd Safri (2006)
We are offering products and services that mainly involve in offset printing. It covers everything from designing to printing and even delivery. We provide services on books publishing, event booklets, pamphlet, brouchers, posters (depend on size), school magazines, wedding cards, postcards, journals, circulars, full scap papers (test pads) and jobs related to printing like designing logos, labels and producing it, name cards and business cards, designing signboards and billboards. We also deal with jobs given by vendors that are usually relatively too small for them. Big printing companies that have accept jobs in small quantity will usually sub-con them to small printing companies like us as using their big machines for small quantities would result in ineffective operation.